2014
DOI: 10.7243/2055-2386-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the reliability of real time ultrasound scanning to measure the humeral head position in a number of glenohumeral joint positions

Abstract: The aim of the current study is to assess the intra-rater and inter-rater reliability of real time ultrasound scanning in measuring static humeral head position. Real time ultrasound scanning, an experimental clinical measurement, was used to record measurements of the humeral head position in a sample of (20) healthy volunteers [9 male, 11 female]. While the participant was seated in a standardized chair, Hips and knees were positioned at 90 degrees of flexion. The humeral head position of each subject was im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Few studies have reported inter-rater reliability for shoulder US image interpretation, in which different raters measure the same set of images. Our study yielded good to excellent inter-rater reliability for image interpretation, in comparison to previous studies that demonstrated only moderate to good reliability for asymptomatic or symptomatic participants ( 8 , 13 , 16 ). The inter-rater reliability of US measurements that we advocate for use in future studies, AHD in neutral position, and SST, SASDB, and SASDB fluid thickness in short axis, all fell within the excellent range for image interpretation.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Few studies have reported inter-rater reliability for shoulder US image interpretation, in which different raters measure the same set of images. Our study yielded good to excellent inter-rater reliability for image interpretation, in comparison to previous studies that demonstrated only moderate to good reliability for asymptomatic or symptomatic participants ( 8 , 13 , 16 ). The inter-rater reliability of US measurements that we advocate for use in future studies, AHD in neutral position, and SST, SASDB, and SASDB fluid thickness in short axis, all fell within the excellent range for image interpretation.…”
Section: Discussioncontrasting
confidence: 50%
“…AHD was originally described for radiographs as the shortest distance between the inferior aspect of the acromion and the humeral head, with RTC abnormalities associated with reductions in AHD secondary to superior migration of the humeral head ( 7 ). AHD is by far the most frequently studied shoulder US measurement in reliability studies of asymptomatic ( 8 13 ) and symptomatic ( 14 22 ) participants, with reported reliability ranging from poor to excellent intra-rater reliability ( 8 12 , 19 22 ), and moderate to excellent inter-rater reliability ( 13 18 ). AGT (acromion-greater tuberosity) distance is the shortest distance between the inferolateral edge of the acromion and the apex of the greater tuberosity and has proven to be useful for examining patients with impingement symptoms ( 23 25 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The translation, in millimetres, is calculated by subtracting the distance between the border of the glenoid (posterior view) or the coracoid process (anterior view), respectively, and the border of the humeral head at rest (condition 1) from the conditions with force applied (conditions 2 and 3). The intrarater and inter-rater reliability of the ultrasound assessment has previously been shown good to excellent in the abducted position from an anterior view (ICC 0.95–0.96 and 0.72–0.8, respectively) and posterior view (ICC 0.98 and 0.77–0.85, respectively) 24. The intrarater and inter-rater reliability with the shoulder in neutral position has also previously been shown to be moderate to excellent (ICC 0.85–0.98 and 0.5–0.75, respectively) 14.…”
Section: Discussionmentioning
confidence: 96%
“…Measures of humeral head position assessing anterior landmarks have been shown to have high levels of intra-tester reliability (ICC 0.93), SEM 0.5-1.0mm, SDD 1.6-2.7mm. 47 …”
Section: Methodsmentioning
confidence: 99%